Implementation of Hifzhul Lisan Ethics and Birrul Muallim in Building Harmonious Teacher-Student Relationships in High Schools - Amsal Qori Dalimunthe; Neng Nurcahyati Sinulingga; Khairuddin Lubis (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2025)
This study aims to analyze communication and ethical crises in teacher-student relationships in senior high schools (SMA) in the digital era, with a focus on the importance of strengthening Hifzhul Lisan and Birrul Muallim ethics as solutions to these problems. The increasing phenomenon of violence in schools, such as mobbing teachers and insults on social media, reflects a moral degradation that can damage the harmony of education. Through a literature study, this research explores the concept of Hifzhul Lisan, which emphasizes polite and correct speech, and Birrul Muallim, which emphasizes respect for teachers as spiritual parents. The results show that applying these two ethics in schools can reduce potential conflicts and build more harmonious relationships between teachers and students. This study also finds the importance of curricular approaches, school culture (hidden curriculum), and collaboration with parents in creating a supportive and civilized educational environment. In addition, the application of technology as a means of literacy can help strengthen Islamic educational values in facing moral and social challenges in the Society 5.0 era. This study concludes that to create character-based and dignified education, there needs to be a reconstruction of the interaction system in high schools based on the ethics of Hifzhul Lisan and Birrul Muallim, which are in line with Islamic spiritual values and national culture.